Take A Trip To Russia - Lye, Keith; Pluckrose, Henry Arthur (London ; F. Watts, 1982)
Text and photographs introduce Russia, the fourth largest country in the world and its leading wheat and steel producer.
Includes index.
Keywords: Soviet Union -- Description and travel; Soviet Union